Primates et Sociétés : La sortie de l’état de nature - Thomas Robert; Gabriela Daly Bezerra de Melo (Revue de Primatologie)
Rousseau’s three centenary is a good opportunity to introduce his fundamental ideas and to apply them to new domains, such as primatology. The concept of the state of nature, developed in the first part of the second Discourse, and the dichotomy between nature and culture that it implies are treated in the different contributions presented in this volume. Historical studies are combined with philosophical investigations in order to emphasis the complex relations between primatologists and their object of study. Even though the different perspectives may diverge from each others, all the contributors insist on the necessity to avoid both anthropocentrism and ethnocentrism in the context of primatology.